SERTIFIKASI HALAL SEBAGAI INSTRUMEN PERLINDUNGAN KONSUMEN DAN PENGUATAN SOSIAL EKONOMI UMKM PENGOLAHAN IKAN DI KABUPATEN SAMBAS - Misbun (Berajah Journal, 2026)
This study analyzes halal certification as an instrument of consumer protection and socio-economic strengthening for fish processing MSMEs in Sambas Regency. The study applies a descriptive qualitative data on the implementation of halal certificates in MSMEs within the fish processing industry. The data are examined by positioning halal certification as a socio-economic practice related to information certainty, consumer trust, product added value, business literacy, certification costs, and the role of local government. The findings show that halal certification functions not merely as administrative proof of product halalness, but also as a consumer protection mechanism that provides assurance over ingredients, production processes, storage, packaging, distribution, sales, and serving. For MSME actors, halal certification may strengthen market legitimacy, improve competitiveness, and increase the economic value of fish-based products such as amplang crackers, salted fish, dried fish, fish crackers, fish balls, and shrimp paste. However, this strengthening has not been evenly realized because many MSMEs still face limited financial capacity, low procedural understanding, weak human resources, and the belief that traditionally produced products are automatically halal. Local government has contributed through socialization and free halal certificate facilitation, yet more structured, continuous, and community-based assistance is needed for coastal household enterprises.